Morphosyntax Errors in Undergraduate Research Articles from English Education Department - Purinanda, Faza Hannan; Sutrisno, Adi; Faza Hannan, Faza Hannan (Universitas Nusantara PGRI Kediri, 2022)
Since the graduates of English education department are expected to be educators, errors that are still prevalent in their research articles need to be acknowledgedas teaching what is essentially flawed language use may lead to damaging results.Therefore, the aim of this research is to inspectprevalent morphological and syntactical errors in undergraduate research articles from English education department and determine the factors causing the errors. The results of the study show that errors are found at both morphological and syntactical levels. The morphological level includes inflection, derivation, preposition, article, possessive determiner, quantifier determiner, copula be, and pronoun. Meanwhile, the syntactical level includes passive voice, tense, infinitive, noun phrase, adverbial clause, adjectival clause, auxiliary, and subject-verb agreement. As for the source of errors, both interlingual and intralingual factors are attributed to causing such errors.This study highlights the process of error classification andthe trend of frequently-made errors, including their commonality within the EFL context. Several suggestions are also offered in order that English learners can be more attentive to their writings. Keywords:error analysis, morpheme, syntax, research article, undergraduate